The Use of Directed Reading Thinking Activity (DRTA) Strategy In Teaching Reading to The Seventh Grade of SMPN 5 Parepare - Riska Ayu Mustika (Pusat Pengembangan Publikasi dan Hak Kekayaan Intelektual Universitas Muhammadiyah Parepare, 2019)
Reading is one of the skills which must be taught to Junior High School students as one of the teaching and learning activities in English class. Reading determines the successful of any subject matters. All depend on the competence of reading comprehension. But in reality, the students argue that reading is not interesting and they are still wrong to understand meaning of the text. They have difficulties in analysis, interpretation and make summary of the text. The students’ need something produced some observation to make them more active and stimulate their interest in order to create an enjoyable atmosphere of English reading activity so that they can build up their reading comprehension particularly to their understanding the content of texts given. The writer uses the interesting strategy to make the students enjoy and more active in the class it is DRTA strategy it can improve the reading comprehension of the students. The objective of the research was to find out whether or not the use of DRTA strategy able to improve the reading comprehension of the seventh grade students of SMPN 5 Parepare. The researcher applied quasi-experimental method, with two groups namely experimental and control class. The sample of class VII1 was 17 students and class VII4 was 13 students, therefore the total number of sample was 30 students. The result of the data analysis showed that there was significant difference of the students reading comprehension before and after teaching using DRTA. The researcher concluded that the use DRTA is effective in improving the reading comprehension of seventh grade students of SMPN 5Parepare. It is proved by the result of the statistical analysis by using application SPSS with applying t-test calculation where the significant value of pre-test (2.311) was lower than the level of significant (2.048) and post-test (2.716) was higher that the level of significant (2.048). Those indicated that H1 was accepted and H0 was rejected. It means that DRTA can improve the reading comprehension of the seventh grade students of SMPN 5 Parepare.